Practical experience of using directly observed procedures, mini clinical evaluation examinations, and peer observation in pre-registration house officer (FY1) trainees. Issue 966 (5th April 2006) - Morris, A; Hewitt, J; Roberts, C M
Abstract : This paper describes an eight month experience with three of the four main assessment tools that will be used to validate the successful completion of the FY1 placement. The practical issues around the implementation of these new tools is of great concern to all involved in the management of postgraduate training and it is hoped that this paper will contribute some of the practical elements so far unavailable from Department of Health sources.